Characterization of femtosecond-laser-induced periodic structures on SiC substrates. (19th January 2018) - Miyagawa, Reina; Ohno, Yutaka; Deura, Momoko; Yonenaga, Ichiro; Eryu, Osamu
Abstract: We investigated the crystalline state of femtosecond-laser-induced periodic structures using a transmission electron microscope (TEM). The core of the 200-nm-pitch periodic nanostructures on SiC retained a high crystalline quality continued from the SiC substrate, where the crystal orientation was aligned with that of the SiC substrate. These results suggest that the periodic nanostructures were formed by periodic etching and not by rearrangement. At high laser power, microstructures with sizes larger than 2 µm were formed on the periodic nanostructures. The microstructures were amorphous and extended from the amorphous SiC layer that covered the periodic nanostructures.